Is Implementing Uganda’s Single Spine Agricultural Extension Reform Feasible? - Barungi, Mildred; Adong, Annet; Guloba, Madina (Economic Policy Research Centre, 2017)
Uganda has undertaken a number of reforms in extension service provision, ranging from a commodity-focused extension system in the colonial times to a farmer demand-driven extension system (National Agricultural Advisory Services-NAADS). Due to the challenges and unsatisfactory impacts associated with NAADS, in 2014 Cabinet approved MAAIF’s position to develop a more integrated, coordinated and harmonized public extension system—the Single Spine agricultural extension service delivery system. However, the feasibility of implementing the Single Spine reform can only be realised if challenges faced by predecessor agricultural extension systems are addressed immediately. This calls for increasing public financing for agricultural extension service delivery or exploring new financing options, recruiting more staff to fill the vacant technical positions, expediting the development of a framework for implementing the Single spine reform, and creating and maintaining good relations among institutions that contribute to delivering extension services to farmers.